We’ve Had Three of Them: Addressing the Invisibility of Lesbian, Gay, Bisexual, and Gender Nonconforming Youths in the Juvenile Justice System - Irvine, Angela (Columbia Journal of Gender and Law, 2010)
Two researchers were speaking to a high-ranking probation officer from a large city, trying to convince her to participate in a project on lesbian, gay, bisexual and questioning (“LGB”), and gender non- conforming youths. Her first response was, “I’ve worked in this system for twenty-five years and in all of that time I think we’ve had three of [these types of youths].” This quote perfectly captures a prevalent myth: the juvenile justice system detains only very few LGB and gender non-conforming youths. Juvenile justice professionals believe this myth because only a handful of LGB and gender non-conforming youths disclose their sexual orientations, act in ways that do not conform to gender norms, or have court cases linked to their sexual orientation, gender identity or gender expression. However, many LGB youths, youths who are questioning their sexual orientations or youths who have non-conforming gender identities enter the juvenile justice system unnoticed. The disproportionate incarceration of youths of color within the juvenile justice system further reinforces the invisibility of LGB and gender non-conforming youths. Many juvenile justice professionals assume that LGB and gender non-conforming youths come from middle class, white families, and therefore, juvenile justice jurisdictions detaining large numbers of youths of color do not serve LGB and gender non-conforming youths. This Article shows that both assumptions are wrong. National survey data presented in this Article shows that fifteen percent of youths in the juvenile justice system are LGB, questioning their sexual orientation, transgender or express their gender in non-conforming ways. Moreover, the data shows that equal proportions of white, African American and Latino youths are LGB and gender non-conforming.